AUDIT LINGKUNGAN SEBAGAI PERWUJUDAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (CORPORATE SOCIAL RESPPONSIBILITY) DI ERA GLOBALISASI EKONOMI - Nur Sulistyo B Ambarini (Masalah-Masalah Hukum, 2011)
Environment audit was both law and economy instruments of protection and environment management. Environment audit was law instrument which have voluntary and mandatory characteristic. Environment audit application periodically and continuity could be the corporate social responsibility realization within economy globalization era. Beside given economy profit and protection to environment (planet), company could develop relationship with local societes and paid attention to the people by doing development activity and used them in order to increasing their prosperity.